Breaking out of isolation : becoming a connected school leader - Cook, Spike C.; Johnson, Jessica (Public school principal); Stager, Theresa (Thousand Oaks : Corwin, 2016)
Fresh ideas to help you overcome leadership isolation! The Corwin Connected Educators series is your key to unlocking the greatest resource available to all educators: other educators. Through powerful vignettes and strategies, you'll discover how innovation-minded school leaders connect to avoid isolation, lower stress, find support, and share ideas. This roadmap to transformational change will help you to: . Strategically connect with colleagues and staff . Jumpstart and sustain your Professional Learning Network . Overcome isolation for lasting impact Being a Connected Educator is more than a set of actions: it's a belief in the potential of technology to fuel lifelong learning. To explore the other books in this series, visit the Corwin Connected Educators website at https://www.corwin.com/connectededucators/'School leadership is a challenge that is made more difficult through isolation, but it doesn't have to be that way. The authors lead you to reflect on what isolates you and share practical ways to help get connected. A must read for connected and soon to be connected leaders!' Todd Whitaker, Professor of Department of Educational Leadership Indiana State University'Filled with real-time examples and reflection questions from three dynamic, active principals who've crafted their own connected and growing practices, this book is a comforting guide for anyone seeking to establish a personal or professional learning network, and lays a Twitter-connected path to the next steps of leadership development.' Kirsten Olson, Ed.D, PCC Author of The Mindful School Leader and Wounded By School.
Includes bibliographical references and index.
Description based on XML content.
Keywords: School management and organization; School administrators -- Job stress -- Prevention; Professional learning communities